Customary Standard of Care: A Challenge for Regulation and Practice - Johnson, Sandra H. (The Hastings Center report, 2013)
Law wrangles with setting and applying standards for the practice of medicine in many different arenas. One of the most prominent is medical malpractice litigation in which the trial process examines a physician's performance and measures it against the standard of care. The profession's prevailing custom, with some substantial tolerance for “respectable minority” views, has been the gold standard for scrutinizing physician practice and treatment decisions in the malpractice context. Using the profession's custom as the measure against which a physician's performance is judged defers to the expertise of medicine. Deference to the medical profession is attractive as a tool for reining in law. Reliance on customary practice is criticized, however, for driving physicians to the relative safety of the middle of the herd. Creating such a strong incentive for compliance with customary practice can dampen medical innovation and the diffusion of new clinical knowledge. The safety of the herd can also deprive individual patients of the best care in their particular circumstances. Several current trends are strengthening claims that professional practice patterns are an inappropriate tool for distinguishing between high-quality and substandard care. In particular, advocacy for evidence-based medicine aggressively asserts that the traditional way of making medical treatment decisions is largely untethered from scientific method or data, rendering professional judgment, even in the aggregate, suspect.